An Initial Estimation of the Economic Effects of the Creation of the EurAsEC Customs Union on Its Members - de Souza, Lucio Vinhas (World Bank, Washington, DC, 2012)
This note provides an initial estimation of some of the economic effects of creating the Eurasian Economic Community (EurAsEC) customs union. Relying on the computable general equilibrium model from the Global Trade Analysis Project (GTAP), results of the simulations consistently support the conclusion that, as an arrangement, the EurAsEC customs union (CU) will be a gross domestic product (GDP)-reducing framework in which the negative trade-diversion effects surpass positive trade-creation ones.